A Novel Negative Pressure, Face-Mounted Antechamber to Minimize Aerosolization of Particles During Endoscopic Skull Base Surgery. Issue 3 (20th May 2021) - Kim, Matthew; Lee, Mark; Schwarz, Justin; Kacker, Ashutosh; Schwartz, Theodore H
Abstract: BACKGROUND: The COVID-19 pandemic has revealed deficiencies in the adequacy of personal protective equipment (PPE) for healthcare workers. Endoscopic endonasal skull base surgery is thought to be among the highest-risk aerosol-generating procedures for surgeons and operating room personnel. OBJECTIVE: To validate the efficacy and clinical feasibility of a novel surgical device. METHODS: A low-cost, modifiable, and easily producible negative pressure, face-mounted antechamber was developed utilizing 3D printing and silicone molding. Efficacy was evaluated using an optical particle sizer to quantify aerosols generated during both cadaver and intraoperative human use with high-speed drilling. RESULTS: Particle counts in the cadaver showed that drilling led to a 2.49-fold increase in particles 0.3 to 5 μm ( P  = .001) and that the chamber was effective at reducing particles to levels not significantly different than baseline. In humans, drilling led to a 37-fold increase in particles 0.3 to 5 μm ( P < .001), and the chamber was effective at reducing particles to a level not significantly different than baseline. Use of the antechamber in 6 complex cases did not interfere with the ability to perform surgery. Patients did not report any facial discomfort after surgery related to antechamber use. CONCLUSION: The use of a negative pressure facial antechamber can effectively reduce aerosolization from endoscopic drilling without disturbing the flow of the operation. The antechamber, in conjunction with appropriate PPE, will be useful during the COVID-19 pandemic, as well as during flu season and any future viral outbreaks.